The Implementation of Project Based Learning in Designing Ecotourism Learning Media - Aboe, Roswita M.; Jusnita, Naniek (STKIP Yapis Dompu, 2022)
The purpose of this study is to describe the implementation of project-based learning in designing Ecotourism learning media and to asses students perception in project based learning application. The study involves 24 respondents of the 6th semester students of English Education Study Program, Khairun University. This study administered questionnaires and evaluation test of writing and speaking as the instrument to collect the data. To analyze the data, this research employed mixed method of quantitative and qualitative descriptive analysis. The result of the analysis of students’ perceptions was described with a likert scale, while students’ achievement from the implementation of Project Based Learning was evaluated by their presentation test. The result of the study showed that 24 respondents obtained 84.72 in their evaluation of writing and speaking test. It is in the category of very good; while from students’ understanding on learning process of a project were 95.14. The suitability of the content in the English for ecotourism course is also in line with project-based learning where there is conformity in the teaching and learning process and was followed by a value of 82.92; while 64.58 score by participants that acknowledge the project based learning increased their skills, motivation and mastery of the material and fostered their learning. In terms of the implementation, students obtained 83.00 of their overall score from presentation test.